Sosialisasi Pendidikan Karakter di Era Digital melalui Media Film Pendek dan Edukasi Screen Time di SDN 2Toyomarto - Rina Alifatul Mutholaah; Nisa Arnianti (JRCE (Journal of Research on Community Engagement), 2026)
Toyomarto Village faced challenges in strengthening character education for elementary school children due to the increasingly intensive use of screen time in this digital era. Students of the Student Work Lecture (KKM) of UIN Maulana Malik Ibrahim Malang responded to this need by conducting an outreach activity at SD Negeri 2 Toyomarto, Singosari District, Malang Regency, on Tuesday, 13 January 2026. The activity began with an educational presentation focusing on character education and screen time management education through the screening of two short films entitled Mana Janji Ayah and Topi: Tindak, Tanduk, Subasita as audio-visual learning media. After the film screenings, an interactive discussion was conducted with the students to explore the character values contained in the films, such as honesty, responsibility, empathy, and compassion. The activity then continued with socialization regarding wise screen time use, including a discussion of positive and negative impacts. In addition to the delivery of the material, the activity also included a question-and-answer session as a form of evaluation and to increase student participation. Through this outreach activity, students were expected to understand the importance of character values and to develop awareness of wise screen time management. The success of this program indicated that a collaborative role among schools, families, and the community was needed to support sustainable character development and children’s digital education.